Use of Optical Coherence Tomography in MI with Non-obstructive Coronary Arteries - Grigoris Karamasis; Iosif Xenogiannis; Charalampos Varlamos; Spyridon Deftereos; Dimitrios Alexopoulos (Interventional Cardiology: Reviews, Research, Resources)
MI with non-obstructive coronary arteries (MINOCA) comprises an important minority of cases of acute MI. Many different causes have been implicated in the pathogenetic mechanism of MINOCA. Optical coherence tomography (OCT) is an indispensable tool for recognising the underlying pathogenetic mechanism when epicardial pathology is suspected. OCT can reliably identify coronary lesions not apparent on conventional coronary angiography and discriminate the various phenotypes. Plaque rupture and plaque erosion are the most frequently found atherosclerotic causes of MINOCA. Furthermore, OCT can contribute to the identification of ischaemic non-atherosclerotic causes of MINOCA, such as spontaneous coronary artery dissection, coronary spasm and lone thrombus. Recognition of the exact cause will enable therapeutic management to be tailored accordingly. The combination of OCT with cardiac magnetic resonance can set a definite diagnosis in the vast majority of MINOCA patients.